Using a decision-making approach to evaluate the effect of accelerators on calcium leaching of sprayed concrete. (August 2022) - Tian, Chong-ming; He, Biao; Ye, Fei; Wang, Jian; Song, Gui-feng
Highlights: The calcium leaching process of shotcrete in the tunnel is successfully imitated through the self-built experimental device. The effect of setting accelerators was successfully evaluated using the developed hybrid decision-making methods. A high pH environment can result in a high degree of calcium leaching. Abstract: The present research aims to figure out the impact of setting accelerators on calcium leaching utilizing a hybrid decision-making method termed entropy weight – technique for order preference by similarity to an ideal solution (EW-TOPSIS). To fulfill this objective, a model test device was developed to carry out the experiment of calcium leaching in sprayed concrete. Three different types of setting accelerators were considered as the control variables in the experiment. Then, Ca 2+ ions concentration, pH value, and flow of drainage solution were considered as indicators to evaluate the effect of each setting accelerator on calcium leaching. Meanwhile, the relationship between the three indicators was analyzed using the response surface method (RSM). Findings showed that relatively high dosing of setting accelerators had an inhibitory effect on calcium leaching of sprayed concrete. Additionally, the environment with a high pH value is more potential to experience calcium leaching.